KINERJA PELAYANAN PERPUSTAKAAN DI DINAS PERPUSTAKAAN DAN ARSIP DAERAH KABUPATEN INDRAGIRI HILIR - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The purpose of this research is to describe the responsiveness of library services, reliability of library services, ethics of library services and library service facilities at the Regional Library and Archives Service of Indragiri Hilir Regency. This research is located at the Regional Library and Archives Service, Indragiri Hilir Regency. This research is a type of qualitative descriptive research. The results of this study are the responsiveness of library services at the Regional Library and Archives Service of Indragiri Hilir Regency is good, there are some user complaints that can be handled as quickly as possible. And all the existing collections according to their location on the shelf with those listed in the online catalog. The reliability of library services at the Regional Library and Archives Service of Indragiri Hilir Regency in terms of the ease of service procedures is quite reliable and not complicated. The ethics of library services at the Regional Library and Archives Service of Indragiri Hilir Regency are good in terms of manners and tidiness. They also serve the patrons selflessly. The library service facilities of the Regional Library and Archives Service of Indragiri Hilir Regency are good, for example related to the available catalogs, so that users do not need to queue if they are going to search for library materials.